Satisfaction and quality of care provided in telemedicine during COVID-19 in a Hospital in Huancayo-Peru 2022 - Vera-Pomalaza, Ninoska L. (2023)
Objective. Establish the relationship between the quality of care received and patient satisfaction in the application of telemedicine during the COVID-19 pandemic at the Hospital Daniel Alcides Carrión de Huancayo in 2022. Methods. a correlational, cross-sectional and quantitative study was carried out on 346 patients over 18 years of age who were treated in 2021 by telemedicine. The variables studied are quality of care and patient satisfaction. Two Likert-type questionnaires were used, which were validated by expert judgment and internal reliability with Cronbach's alpha. For the inferential correlation analysis, normality was evaluated with the Kolmogorov-Smirnov test and, according to the result, the non-parametric statistical test of Spearman's Rho was used with a p value less than 0.05. Results. The results show that 98.6% of patients are highly satisfied with telemedicine and 94.2% perceive high quality of care. On the other hand, the direct and moderately significant relationship between the patient satisfaction variables and the quality of care was confirmed with the R2 determination coefficient equal to 0.372. In addition, it was validated with a Rho Spearman coefficient equal to 0.541 that there is a moderate direct correlation in the general hypothesis and for the specific hypotheses, it is direct low and direct moderate since the Rho Spearman coefficients are between 0.279 and 0.466. Conclusions. A better quality of telemedicine care determines better patient satisfaction in all its dimensions.